The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1371/journal.pone.0241768
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of first line antiretroviral therapy treatment failure and associated factors among adult patients on ART in South West Shoa, Central Ethiopia

Abstract: Background First-line antiretroviral treatment failure has become a public health concern in high, low and middle-income countries with high mortality and morbidity In Ethiopia, around 710,000 peoples were living with HIV and 420,000 of them were receiving ART in 2017. Little is known about the magnitude of first-line ART treatment failure and its associated factors in Ethiopia, particularly in the study area. Therefore, this study was aimed to find the magnitude of first-line ART treatment failure and its ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
(25 reference statements)
4
2
0
Order By: Relevance
“…Further, we demonstrated that low CD4 + cell count (baseline CD4 + cell count of <50 and ≤100 cells/ µl) were associated with increased odds of VF. Comparable results have been reported in Ethiopia [26, [33][34][35], and Kenya [36], among others. To explain this relationship, the inverse relationship between CD4 + cell count and viral replication at speci c stages of the disease has been invoked [33].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Further, we demonstrated that low CD4 + cell count (baseline CD4 + cell count of <50 and ≤100 cells/ µl) were associated with increased odds of VF. Comparable results have been reported in Ethiopia [26, [33][34][35], and Kenya [36], among others. To explain this relationship, the inverse relationship between CD4 + cell count and viral replication at speci c stages of the disease has been invoked [33].…”
Section: Discussionsupporting
confidence: 64%
“…Comparable results have been reported in Ethiopia [26, [33][34][35], and Kenya [36], among others. To explain this relationship, the inverse relationship between CD4 + cell count and viral replication at speci c stages of the disease has been invoked [33]. In addition, a low CD4 + cell count is a marker of advanced disease, hence the potential presence of HIV-de ning infections.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Further, we demonstrated that low CD4 + cell count (baseline CD4 + cell count of < 50 and ≤ 100 cells/ µl) were associated with increased odds of TF. Comparable results have been reported in Ethiopia [ 27 , 34 36 ], and Kenya [ 37 ], among others. To explain this relationship, the inverse relationship between CD4 + cell count and viral replication at specific stages of the disease has been invoked [ 34 ].…”
Section: Discussionsupporting
confidence: 63%
“…First line ARV failure was reported in studies conducted in Addis Ababa and Gondar [35][36][37]. Presence of opportunistic infection, no formal education, low CD4 count and patients having respiratory infection like tuberculosis are important predictors of treatment failure among HIV patients [35,36,38,39]. Staphylococcus aureus is normal human bacterial flora and is considered as a cause of a wide range of opportunistic…”
Section: Plos Global Public Healthmentioning
confidence: 99%